2020
DOI: 10.1093/mnras/staa235
|View full text |Cite
|
Sign up to set email alerts
|

A large catalogue of molecular clouds with accurate distances within 4 kpc of the Galactic disc

Abstract: We present a large, homogeneous catalogue of molecular clouds within 4 kpc from the Sun at low Galactic latitudes (|b| ă 10˝) with unprecedented accurate distance determinations. Based on the three-dimensional dust reddening map and estimates of colour excesses and distances of over 32 million stars presented in Chen et al, we have identified 567 dust/molecular clouds with a hierarchical structure identification method and obtained their distance estimates by a dust model fitting algorithm. The typical distanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 42 publications
2
40
0
1
Order By: Relevance
“…Based on a sample of over 32 million stars with color excesses and Gaia distances, Chen et al (2019b) constructed new three-dimensional dust reddening maps of the Milky Way. With the maps and the sample of stars, Chen et al (2020) identified 567 dust/molecular clouds, and estimated their distances by using a dust model fitting algorithm. The typical distance uncertainty was less than 5%.…”
Section: Giant Molecular Cloudsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a sample of over 32 million stars with color excesses and Gaia distances, Chen et al (2019b) constructed new three-dimensional dust reddening maps of the Milky Way. With the maps and the sample of stars, Chen et al (2020) identified 567 dust/molecular clouds, and estimated their distances by using a dust model fitting algorithm. The typical distance uncertainty was less than 5%.…”
Section: Giant Molecular Cloudsmentioning
confidence: 99%
“…Accurate parallaxes and proper motions have been obtained for a large number of HMSFR masers (e.g., Reid et al, 2019), HII regions (e.g., , O-type stars (e.g., Xu et al, 2021), young open clusters (OCs, e.g., Dias et al, 2021), and evolved stars (e.g., Khoperskov et al, 2020). Additionally, many giant molecular clouds (GMCs) have had accurately determined distances based on the multi-wavelength survey data from optical to infrared bands or the astrometric data of foreground/background stars (Yan et al, 2019;Chen et al, 2020). By combining the available data of different types of tracers together, it is now possible to reliably map the detailed spiral structure within about 5 kpc of the Sun.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of these cores have been recalculated using the same assumptions outlined in this work (section 4.1). (lower panel) Shown as grey open points are the properties taken directly fromLarson (1981),Kauffmann et al (2013), Peretto et al (2013), Sánchez- Monge et al (2013), and Chen et al (2020. Overlaid as diagonal solid black lines are the mass-radius relations taken fromLarson (1981, L81), and high-mass star formation thresholds taken fromKrumholz & McKee (2008, KM08) andKauffmann & Pillai (2010, KP10).…”
mentioning
confidence: 99%
“…In the current work, we have adopted a method similar as in the work of Chen et al (2020a). The method comprises three steps: the first step is to isolate the individual molecular clouds from the 3D extinction maps; the second step to estimate the distances of the identified molecular clouds; and the third step to calculate their physical properties.…”
Section: Methodsmentioning
confidence: 99%
“…Using similar techniques, Zucker et al (2019Zucker et al ( , 2020 measured the distances of local molecular clouds by combining the optical and near-IR photometries with the Gaia Data Release 2 (Gaia DR2; Gaia Collaboration 2018). Recently, Chen et al (2020a) presented a large catalogue of 567 clouds in the Galactic plane identified from the 3D extinction maps of Chen et al (2019) and provided their accurate distances and other physical parameters.…”
Section: Introductionmentioning
confidence: 99%